Adapting Uncertainty Reduction Theory for Crisis Communication: Guidelines for Technical Communicators. (January 2021) - Grace, Rob; Tham, Jason Chew Kit
The central components of an interpersonal communication framework such as uncertainty reduction theory can be adapted to design and evaluate crisis communication addressing uncertainty between citizens needing access to services and organizations attempting to manage risk and ensure continuity of operations. Through a content analysis of organizational crisis communication during the COVID-19 pandemic, this article adapts uncertainty reduction theory as an applied, user-centered framework that can guide technical communicators in managing uncertainty during unprecedented crises.